Sisi's Regime: Military Domination of Egypt's Economy - Cahyani Cahyani; Salma Salsabila; Mulawarman Hannase (Publik : (Jurnal Ilmu Administrasi), 2022)
Egypt's economy has been stagnant since the January 2011 revolution, who overthrew the president at that time, Hosni Mubarak. In March 2014, Abdel Fattah el-Sisi announced his intention to run for president of Egypt. All kinds of deficits such as budget, and trade have reached alarming levels. The purpose of this research is to describe the steps of the Sisi regime in implementing authoritarian principles and (2) to describe the economic progress felt by the Egyptian people with the application of these principles. The research method used in this study is content analysis. The data used is primary data from texts relevant to the research title. The research shows that Sisi's military leadership is indeed strong in the presidency. However, this has not been successful in attracting investment from other countries due to the unstable political situation. The people hope that Sisi will create jobs for them and ensure economic and political stability. This will allow the Egyptian economy to improve along with a conducive situation and the influx of foreign investment, which can support the development of the private business sector.